2022
DOI: 10.1111/pcn.13337
|View full text |Cite
|
Sign up to set email alerts
|

Cross disorder comparisons of brain structure in schizophrenia, bipolar disorder, major depressive disorder, and 22q11.2 deletion syndrome: A review of ENIGMA findings

Abstract: This review compares the main brain abnormalities in schizophrenia (SZ), bipolar disorder (BD), major depressive disorder (MDD), and 22q11.2 Deletion Syndrome (22q11DS) determined by ENIGMA (Enhancing Neuro Imaging Genetics through Meta Analysis) consortium investigations. We obtained ranked effect sizes for subcortical volumes, regional cortical thickness, cortical surface area, and diffusion tensor imaging abnormalities, comparing each of these disorders relative to healthy controls. In addition, the studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 49 publications
(32 citation statements)
references
References 119 publications
(203 reference statements)
4
28
0
Order By: Relevance
“…Studies combining results of single-disorder ENIGMA meta-analyses were able to take a more fine-grained approach to cortical regions, but examined only six disorders, meaning they were not able to comment on disorders including PTSD, anxiety disorders, psychotic depression, schizoaffective disorder or borderline personality disorder 4,6,16 . In keeping with the current findings, these prior studies found shared patterns of grey matter loss across disorders, with more severe cortical loss and enlargement of the pallidum in schizophrenia.…”
Section: Articlementioning
confidence: 99%
“…Studies combining results of single-disorder ENIGMA meta-analyses were able to take a more fine-grained approach to cortical regions, but examined only six disorders, meaning they were not able to comment on disorders including PTSD, anxiety disorders, psychotic depression, schizoaffective disorder or borderline personality disorder 4,6,16 . In keeping with the current findings, these prior studies found shared patterns of grey matter loss across disorders, with more severe cortical loss and enlargement of the pallidum in schizophrenia.…”
Section: Articlementioning
confidence: 99%
“…In the raw data models, which were residualized of covariates including site, sex, and linear +quadratic effects of age and head motion (only included for functional models), we observe no group differences after multiple comparison corrections. The lack of any group differences in the raw data was initially a puzzling finding due to reported group differences in the literature ( Arbabshirani et al, 2013 ; Cetin et al, 2015 ; Cetin et al, 2016 ; Cheon et al, 2022 ; Dansereau et al, 2017 ; Howes et al, 2023 ; Lei et al, 2020a ; Lei et al, 2020b ; Meng et al, 2017 ; Rahim et al, 2017 ; Rosa et al, 2015 ; Salvador et al, 2017 ; Shi et al, 2021 ; van Erp et al, 2018 ; Venkataraman et al, 2012 ; Wannan et al, 2019 ; Yu et al, 2012 ), however, upon the investigation of the uncorrected statistical maps, we observe that the raw data follows a similar pattern to the deviation group difference map ( Figure 4 ), but these results do not withstand multiple comparison correction. For full statistics including the corrected and uncorrected p-values and test-statistic of every ROI, see Supplementary files 3 and 4 .…”
Section: Resultsmentioning
confidence: 99%
“…1 In the Enhancing Neuroimaging Genetics through Meta-Analysis (ENIGMA) consortium project, morphological indices such as subcortical volume, cortical thickness, and cortical surface area were compared with healthy subjects in schizophrenia (SZ), bipolar disorder (BD), and major depressive disorder (MDD). 2 The direction of the effect size is the same for all measures and the degree of impairment is SZ > BD > MDD. The effect sizes are averages for each disease group, and even SZ, which has the highest level of disability, has an effect size (Cohen's D) of only 0.5 at best, and its distribution shows overlap with that of healthy subjects.…”
mentioning
confidence: 91%
“…The Enhancing Neuroimaging Genetics through Meta‐Analysis (ENIGMA) consortium project is an international collaborative research system launched in 2009, and the Cognitive Genetics Collaborative Research Organization (COCORO) is a Japanese multicenter collaborative research system launched in 2013 1 . In the Enhancing Neuroimaging Genetics through Meta‐Analysis (ENIGMA) consortium project, morphological indices such as subcortical volume, cortical thickness, and cortical surface area were compared with healthy subjects in schizophrenia (SZ), bipolar disorder (BD), and major depressive disorder (MDD) 2 . The direction of the effect size is the same for all measures and the degree of impairment is SZ > BD > MDD.…”
mentioning
confidence: 99%